Philosophy for children as a tool for revitalizing Philippine basic education - Marquez, Leander Penaso
This paper does not aim to prove why Philosophy for Children should be used in Philippine basic education classrooms. Rather, it aims to show how it can be used inside the classroom given the conduct of the Philippine K to 12 program curriculum. One of the criticisms against Philosophy for Children is that it can be totalitarian when applied to contexts that are different from those of the western world since it was developed in the West for the needs and the context of the West. Accordingly, practitioners of P4C in many parts of the world try to “reinvent” the pedagogy to cater to the demands of their respective educational contexts. More often, this reinvention is characterized by a change in stimulus, that is, from philosophical novels written by Lipman to novels or stories (or other forms of philosophical stimuli) that are more relatable to the members of the community of inquiry as determined by the milieu of their respective countries. In this light, this paper tries to go beyond simply reinventing the P4C pedagogy but offers avenues to integrate it in the conduct of the Philippine K to 12 education. In particular, this paper presents two models, namely: 1) Philosophical Lesson Planning model or the STAR Lesson Plan and 2) Philosophical Textbook Writing model. These models can easily be adapted to any educational milieu and, consequently, P4C practitioners from any part of the world can directly and easily apply these models in their respective educational situations.